Design Of Class Vii Informatics Learning Media Using Adobe Animate In MTSN 6 AGAM - Aikal, Fikri (Journal of World Science, 2022)
This research aims to develop and produce computer based learning media using adobe animate application in informatics subjects. Learning media has a very important role in learning. This research uses the 4D version of the Research and Development (R&D) method, namely Define, Design, Development, and Disseminate. The multimedia development model use is the luther sutupo version model which has six stage, namely concept, design, material collection, assembly, testing, and distribution. The result of this study showed (1) validation test by three lecturers in computer informatics engineering expeerts showed a value of 0, 94 with a very valid category, (2) practicality tests from three informatics subject teachers showed a score of 0,95 showed very practical, (3) the effectiveness test of 25 students showed a score of 0,90 showed very effective